Alzheimer’s disease: where do we stand now and what are the strategic interventions? - González, Andrea; Geywitz, Stephanie; Maccioni, Ricardo B. (Frontiers in Cellular Neuroscience, 2025)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative disease, the primary cause of dementia in people over 65 years old. AD is characterized by two molecular hallmarks, the intracellular neurofibrillary tangles of tau and amyloid beta oligomers, which are aggregates of hyperphosphorylated tau and amyloid beta peptides, respectively. These hallmarks gave rise to the two main theories that have opened the way for available treatments, such as FDA-approved memantine, and Aβ (aducanumab, lecanemab) and tau immunotherapies. Tau immunotherapy, especially multitarget approaches, has been recently proven effective. However, drugs against amyloid plaques had a non-successful outcome, despite their contributions to AD knowledge. An innovative approach comes from the multitarget concept, based on bioactive molecules and nutraceuticals. Interestingly, the use of early detection biomarkers such as Alz-Tau®, SIMOA®, and the recent Lumipulse™ test, are an important support to orient AD therapies based on the modifications of the styles of life. This includes physical exercise, a healthy diet, mindfulness, and cognitive stimulation, among others. All of the above analyses are critical to switch the focus to the prevention of AD.